2015
DOI: 10.1002/lary.25608
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized tissue transfer in head and neck surgery: Is intensive care unit–based management necessary?

Abstract: We demonstrate that care in a non-intensive care setting following vascularized free tissue transfer is safe, less costly, and decreases length of hospital stay compared to routine intensive care-based management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
6
39
0
1
Order By: Relevance
“…Patients necessitating subsequent ICU transfer required escalation of care primarily for medical, rather than surgical, concerns. Complication rates were comparable to those reported in the literature, both among prior cohorts cared for in intensive care and non‐intensive care settings . Multivariable regression analysis identified the presence of multiple medical comorbidities and heavy alcohol consumption as factors associated with greater odds of ICU transfer, consistent with a prior study demonstrating increased complications after head and neck free flap reconstruction among patients with alcohol withdrawal syndrome …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Patients necessitating subsequent ICU transfer required escalation of care primarily for medical, rather than surgical, concerns. Complication rates were comparable to those reported in the literature, both among prior cohorts cared for in intensive care and non‐intensive care settings . Multivariable regression analysis identified the presence of multiple medical comorbidities and heavy alcohol consumption as factors associated with greater odds of ICU transfer, consistent with a prior study demonstrating increased complications after head and neck free flap reconstruction among patients with alcohol withdrawal syndrome …”
Section: Discussionsupporting
confidence: 81%
“…Additionally, the average cost per patient was $3238 higher in patients transferred to the ICU. Panwar et al performed a retrospective review of 72 patients in a non‐ICU protocol compared to 175 patients in an ICU protocol and similarly found that avoiding the ICU was associated with shorter hospital stays and substantially less hospital charges . These studies provide further valuable information regarding the length of stay and cost by virtue of having a comparator arm of patients transferred to the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of specialized head and neck surgery units with deliberate training and expertise in H&N free tissue transfer patients, including free flap monitoring and tracheostomy care, have successfully allowed immediate postoperative recovery on the general care floor. This transition away from ICU recovery has been studied and shows decreased hospital stay lengths, decreased cost, and no changes in flap survival or inpatient morbidity . Our study found a slight advantage in reported MFTT success for patients going to floor or step‐down unit (97.0% vs 95.3% for ICU‐level care), and no differences in reported complication rates were observed.…”
Section: Discussionmentioning
confidence: 48%
“…Variables contributing to differences in patient disposition may include specific hospital policies regarding frequency of monitoring, number of free tissue transfers performed at each hospital per year, and nursing comfort or familiarity with MFTT patients. A cost analysis of postoperative care for free flap patients by Panwar et al found an increased cost of 38% over the course of hospitalization attributable to short‐term immediate postoperative ICU care . With this in mind, efforts at improving nursing comfort and tailoring policies that support immediate bypass of, or early transfer from, the ICU could help decrease the overall significant financial costs of free tissue transfer.…”
Section: Discussionmentioning
confidence: 99%